Pengaruh Keikutsertaan Dalam Kelas Ibu Hamil Terhadap Rentang Waktu Penggunaan Kontrasepsi di Puskesmas Umbulharjo I, Yogyakarta Tahun 2016 - Riska Ismawati Hakim; Dyah Noviawati Setya Arum; Tri Maryani (Jurnal Kesehatan Ibu dan Anak, 2017)
RETRACTED Following rigorous and careful concerns and consideration in the review of the article published in Jurnal Kesehatan Ibu dan Anak entitled “Pengaruh Keikutsertaan Dalam Kelas Ibu Hamil Terhadap Rentang Waktu Penggunaan Kontrasepsi di Puskesmas Umbulharjo I, Yogyakarta Tahun 2016” Vol 11, No 1, Juli 2017, DOI: https://doi.org/10.29238/kia.v11i1.42 The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Jurnal Teknologi Kesehatan, Vol. 13, No. 1, Maret 2017 This paper has been found to violate the principles of Jurnal Kesehatan Ibu dan Anak publication and has been retracted.